FORENSIC SCIENCE AND CRIMINAL JUSTICE SYSTEM: A COMPREHENSIVE STUDY (International Journal of Food and Nutritional Sciences, 2022)
Forensic science is a multidisciplinary field that uses scientific methods to investigate and solvecrimes. It involves the collection, analysis, and interpretation of physical evidence from crimescenes, such as fingerprints, DNA samples, fibers, and firearms.